Analisis Campur Kode dalam Novel Ney Dawai Cinta Biola Karya Hadi S.Khuli dan Implementasi dalam Pembelajaran Bahasa Indonesia SMP Kelas VIII - Sari, Ayu Nita, Drs. Atiqa Sabardila, M. Hum (2017)
The purpose of this study was to determine: (a) Determine the existing code-mixing in the novel Love Violin Strings Ney Hadi S. Khuli work. (B) Knowing the function of code-mixing that occurs in the conversation in the novel Love Violin Strings Ney Hadi S. Khuli work. (B) Knowing the implementation of code-mixing in the novel entitled Love Violin Strings Ney Hadi S. Khuli work as teaching materials Indonesian junior class VIII. The research is a qualitative study using descriptive methods. The data source of this research is novel Ney Love Violin Strings Hadi S. Khuli work. Data in the form of dialogue that contain code-mixing. The data collection technique using the technique see and record. Test the validity of the data using triangulation theory. Analysis of the data in this study using. Mix the most dominant code is in Java language code analysis intangibles that obtain 36 data. Mixed tangible code Arabic that there are 8 data. Acquisition of English code-mixing that there are 5 data. Related sociological studies of Indonesian material can be used as teaching materials in the junior class VIII. Keywords: code-mixing, and learning Indonesian